(untitled) (Web of Teachers: Inderscience Research, 2025)
The article provides information on acquiring and consolidating knowledge that constitutes the theoretical foundation of sports activity, expanding the fund of motor skills and abilities that create favorable conditions for improvement in the chosen sport, and developing skills and abilities that are part of the chosen sports technique and tactics.